Effects of School Activities on the Holistic Development of Intermediate Pupils in Selected Private Schools - Villaflores, Jerome (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of school activities on the holistic development of intermediate pupils in selected private schools using a descriptive survey research design. The respondents were primarily Grade Five pupils aged 11 years old, mostly male, belonging to small family sizes with parents who were college graduates and earning moderate to high monthly income levels. Findings revealed that school activities had a high extent of effects on cognitive, social, emotional, physical, and moral development of pupils. Participants commonly engaged in outreach and community service activities, which further enhanced their interpersonal skills and sense of responsibility. Statistical analysis showed no significant differences in most developmental domains when grouped according to demographic profiles, except for emotional development which varied significantly according to grade level and mother’s occupation. Moreover, students reported challenges such as fear of poor performance, limited time due to academic workload, and low confidence in participating in activities. These findings suggest that school activities play a crucial role in shaping holistic development while highlighting the influence of maturity and maternal occupational background on emotional growth. Therefore, it is recommended that school administrators strengthen the planning and evaluation of school programs to ensure alignment with holistic development goals, allocate adequate resources for inclusive participation, and provide guidance and support systems that address pupils’ emotional needs and encourage active engagement in diverse activities. The study further emphasizes the importance of holistic education in fostering well-rounded learners who are academically competent and socially responsible within their communities. This highlights the need for sustained collaboration among teachers, parents, and stakeholders to maximize the benefits of school activities in student development programs. Ultimately this research contributes to evidence-based educational planning and supports continuous improvement of school activity implementation for holistic learner growth in selected private school settings across developmental domains effectively long term.